Encyclopedia of conflict resolution - Burgess, Heidi (ABC-CLIO, 1997)
In the Encyclopedia of Conflict Resolution, field specialists Heidi Burgess and Guy M. Burgess define conflict resolution broadly, covering both long-running, deep-rooted conflicts such as the abortion rights issue and short-term, negotiable disputes such as those between seller and consumer. But conflict arises in many contexts - personal, organizational, business, community, and international - all of which are covered here in depth.